Pengaruh Kepemimpinan Dan Sistem Shift Kerja Terhadap Work-Life Balance Karyawan SPBU Di Kecamatan Seluma Barat - Listika Listika; Sulisti Afriani; Iswidana Utama Putra (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi, 2026)
Work-life balance is an important aspect in creating employee well-being, particularly in the service sector that implements shift work systems such as gas stations. The balance between work demands and personal life is strongly influenced by leadership style and work schedule arrangements. Inappropriate leadership and poorly managed shift work systems may lead to work stress, fatigue, and a decline in employees’ quality of life.The purpose of this study is to analyze the effect of leadership and shift work systems on employees’ work-life balance, both partially and simultaneously, at gas stations in West Seluma District. This study is expected to provide empirical evidence regarding the role of leadership and shift work arrangements in supporting the balance between employees’ work responsibilities and personal lives..This study employed a quantitative approach using a total sampling technique involving 35 respondents. Data were collected through questionnaires that had been tested for validity and reliability. Data analysis was conducted using multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination with the assistance of SPSS software.The results showed that leadership has a positive and significant effect on employees’ work-life balance (Sig = 0.043), and the shift work system also has a positive and significant effect (Sig = 0.000). Simultaneously, both variables significantly affect work-life balance, as indicated by an F value of 191.267 with a significance level of 0.000. The coefficient of determination (R²) value of 0.923 indicates that 92.3% of the variation in work-life balance is influenced by leadership and shift work systems. Therefore, supportive leadership and fair, proportional shift work arrangements are important factors in maintaining employees’ work-life balance at gas stations.